Consumer attributions for corporate social responsibility: causes and consequences - Kajenthiran, K.; Achchuthan, S.; Umanakenan, R.; Sivanenthira, S. (Society and Business Review - Emerald Publishing, 2022)
Purpose – This study aims to investigate the complex relationship between corporate social responsibility (CSR) dimensions and customer loyalty. In particular, this study suggested an intervening process through customer perceived value, which makes banking customers more loyal. Design/methodology/approach – Using a randomised sample of 261 respondents from the Northern Province of Sri Lanka, this study empirically investigates the role of CSR in enhancing customer value and loyalty. The collected data, the study model and hypotheses were assessed by partial least squares structural equation modelling. Findings – According to the results, CSR practices that are both strategic and stakeholder-driven have a positive effect on customer loyalty in the banking industry. Further, customer perceived-value positively impacts customer loyalty. Besides, customer perceived-value mediates the association between CSR practices and customer loyalty. Research limitations/implications – This study is limited to the banking industry. Thus, future studies can replicate the same research in different sectors like retail, tourism and hospitality, insurance and microcredit institutions, garments, textiles, etc. Practical implications – This study suggests specific dimensions of CSR that need to be emphasised while the banking industry designs its loyalty programs. Originality/value – The notion of customer value has been suggested as a mediating mechanism between diversified CSR perspectives and customer loyalty. Thus, this study proposes a comprehensive framework for enhancing customer loyalty to banks via CSR practices and customer value creation.
Keywords: Corporate social responsibility (CSR); Customer loyalty; Customer perceived value; Banks